Upaya Meningkatkan Kemampuan Membaca Permulaan Melalui Media Audio Visual pada Anak Usia 5-6 Tahun di Ra An-Nida - Zahra Yunita; Nurmawati Nurmawati; Inom Nasution (Institut Nalanda, 2024)
The purpose of this study is to determine (1) whether the audio-visual materials in RA AN-NIDA can help children aged 5-6 years with early reading. (2) the capacity of children aged 5 to 6 years to develop their reading skills after using audiovisual media. (3) The use of audiovisual materials in the first reading material with the topic of introducing fruits with alphabetic letters in RA-ANNIDA can improve early reading skills of children aged 5-6 years. This study uses the Classroom Action research design. 17 children in RA AN-NIDA aged 5-6 years were study participants. Considering the findings of the study, which according to the pre-test results, only two children showed growth. With a classical proportion of 11%, the average score achieved was 1.70, indicating that the other 15 children were not yet developed. (2) Only ten children made progress in the first cycle, while seven additional children, with an average score of 2.64 and a classical proportion of 58%, had not. Then, with an average score of 3 and a classical development percentage of 100%, there were 17 children who had developed in the second cycle, compared to 0 who had not developed. According to the information above, audiovisual media can help children who are five or six years old with their initial reading ability